OBSERVATIONS ON THE MULLET FISHERY IN THE HOOGHLY AND MAHANADI ESTUARINE SYSTEMS - Thakur, Nirmal K (Indian Journal of Fisheries, 2011)
Trends of mullet fishery have been studied on the basis of recorded data fromthe Hooghly estuary (1959-66) and the Mahanadi estuary (1962-64). The size structureof different speciet in the catches and the fluctuations therein have been examined. Areasof fishing and fishing,methods have been described. Attempts have been made to correlatethe fluctuations of landings of tlifferent species with certain environmental features.